2022
DOI: 10.1029/2022gc010597
|View full text |Cite
|
Sign up to set email alerts
|

How Slab Age and Width Combine to Dictate the Dynamics and Evolution of Subduction Systems: A 3‐D Spherical Study

Abstract: During subduction, the oceanic lithosphere of one tectonic plate dives beneath another at a convergent margin and is recycled into Earth's mantle (e.g., Kearey et al., 2009;Stern, 2002). As subducted slabs descend, their negative buoyancy provides a key driving force for plate tectonics, and they continue to influence surface processes in a number of ways (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 111 publications
4
38
0
Order By: Relevance
“…Most notably, the overriding plate (OP) is neglected. This is due to resolution limitations but in line with other time-dependent subduction models within a global domain (Chamolly & Ribe, 2021;Chen et al, 2022;Morra et al, 2009Morra et al, , 2012. Including an OP would reduce the rate of trench retreat relative to SP motion (Butterworth et al, 2012;Yamato et al, 2009) and shift the mantle wedge corner (and hence negative pressure associated with corner flow) to greater depth.…”
Section: Modeling Limitationsmentioning
confidence: 54%
See 2 more Smart Citations
“…Most notably, the overriding plate (OP) is neglected. This is due to resolution limitations but in line with other time-dependent subduction models within a global domain (Chamolly & Ribe, 2021;Chen et al, 2022;Morra et al, 2009Morra et al, , 2012. Including an OP would reduce the rate of trench retreat relative to SP motion (Butterworth et al, 2012;Yamato et al, 2009) and shift the mantle wedge corner (and hence negative pressure associated with corner flow) to greater depth.…”
Section: Modeling Limitationsmentioning
confidence: 54%
“…I use a simplified geometrical, mechanical, and rheological setup and neglect the overriding plate (cf. Chamolly & Ribe, 2021;Chen et al, 2022;Morra et al, 2012). Subduction is initiated by allowing a notch to extend to an initial depth of 150 km with a 250 km radius of curvature (Figure 1).…”
Section: Geometric and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The subducting lithosphere comprises a 2,200 km-long composite plate of constant initial thickness (h = 70 km) with a core isoviscous layer (h c = 30 km) embedded in upper and lower visco-plastic layers with viscosities that follow a von Mises law, consistent with the reference plate in Chen et al (2022). Upper and lower visco-plastic layers approximate the strain-rate weakening that occurs above and below the slab core in thermo-mechanical simulations of subduction (e.g., Garel et al, 2014), following OzBench et al (2008.…”
Section: Model Setupmentioning
confidence: 98%
“…Previous geodynamic modelling studies have shown the wide variety of physical parameters that influence subduction processes, such as the slab thickness (Bellahsen et al, 2005;Capitanio & Morra, 2012;F. Chen et al, 2022;Funiciello et al, 2008;Stegman et al, 2010) and length (A. F. Holt & Becker, 2016;Xue et al, 2020), the mantle rheology (A. F. Holt & Becker, 2016;Pusok et al, 2018), the strength and thickness of the overriding plate (OP) (Butterworth et al, 2012;Hertgen et al, 2020;A.…”
Section: Introductionmentioning
confidence: 99%